Echinoderms Metabolites: Structure, Functions and Biomedical Perspectives II - Kalinin, Vladimir I.; Silchenko, Alexanra S. (MDPI - Multidisciplinary Digital Publishing Institute, 2022)
The book largely reflect the structural diversity of echinoderm metabolites including triterpene glycosides and fucosylated chondroitin sulfates, as well as branched fatty acids, di- and triacylglycerols and other lipid classes from the sea cucumbers, polyhydroxysteroids from starfish and different classes of sphingolipids from sea cucumbers and starfish. Finally, the MS-based metabolomic approach, which is very helpful for the estimation of such diversity, is discussed. The materials from the Special Issue also illustrate the biomedical potential of the presented metabolites as cytotoxins and anticoagulants. The in silico approach broadens the possibilities to investigate the mechanisms of the action of membranolytic compounds.